11. SOME FACTORS RELATED TO HOSPITAL-ACQUIRED INFECTIONS AT THE INTENSIVE CARE DEPARTMENT OF NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Subjects and Methods: Identify some factors related to hospital-acquired infections in the Intensive Care Department of Nghe An Obstetrics and Children's Hospital in 2024. Results: Among 306 patients meeting research criteria in 3 intensive care units, the rate of hospital-acquired infections was 10.8%. Factors related to the possibility of hospital-acquired infections include: Age, area of ​​residence, gestational age at birth, presence of underlying/chronic diseases, length of treatment in the intensive care unit length and number of invasive interventions/procedures on patients with p
Keywords: Nosocomial infections; Intensive Care Unit; Nghe An Obstetrics and Pediatrics Hospital